Knowledge, Attitude and Practice Of Self Medication (Self Drugs Prescription) Among Students In Al-Qadisiyah University/ College Of Medicine - Israa Mahmood Abd Al-Zihra; Fatima Abd Alkathem Redha Alkhalidi (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Background: Self-medication is defined as using medicinal products to treat the disorders or symptoms diagnosed by oneself, Self-Medication is common practice worldwide in both developed and developing countries, Regulations usually distinguish between prescription-only medicines (POM) and over the counter (OTC) drugs. inappropriate self-treatment can pose various risks including drug side effects, recurrence of symptoms, drug resistance, etc. the purpose of this study was to investigate the knowledge, attitude, and practice of medical students towards self-medication.  Subjects and Methods: A cross-sectional study was carried out among five stages that were selected by the simple random sampling for choosing the students. Data collections were performed from the beginning of March to October 2023. Data were collected with A four-part researcher questionnaire. It was designed to address the students’ knowledge, attitude, and practice. Statistical analysis was performed using Statistical Package for the Social Sciences 23 software. Results: Out of 462 questionnaires distributed, 445 questionnaires were completed; giving a response rate of 96.3%. According to the results, 310 (69.7%) students had carried out self-medication within the past one year. Common cold was the most common ailment treated with self-medication (73.9%) and antipyretics analgesics (64.5%) were the most used drugs. The primary information sources used by the students were their academic knowledge and books (47.4%). Health problems are not serious the most reason for self-medication in the study and lack of knowledge about medicine the highest causes for not taking medication. Conclusion: students’ knowledge of self-medication appears to be good and significantly high. As well self-medication was highly practiced among the students. Therefore, medical students should be viewed as important contributors to the public health care system, and future health professionals should be properly educated on good pharmacy practice and responsible self-medication.